2012
DOI: 10.1002/14651858.cd007179.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for treating human brucellosis

Abstract: Doxycycline (six weeks) plus streptomycin (two or three weeks) regimen is more effective regimen than doxycycline plus rifampicin (six weeks) regimen. Since it needs daily intramuscular (IM) injection, access to care and cost are important factors in deciding between two choices. Quinolone plus rifampicin (six weeks) regimen is slightly better tolerated than doxycycline plus rifampicin, and low quality evidence did not show any difference in overall effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 48 publications
2
77
0
13
Order By: Relevance
“…These findings were confirmed by two more systematic reviews 26,27 . In the same year, a systematic review published by the Cochrane Group suggested the same treatment combination, however, with streptomycin as the aminoglycoside of choice 28 .…”
Section: Treatmentmentioning
confidence: 99%
“…These findings were confirmed by two more systematic reviews 26,27 . In the same year, a systematic review published by the Cochrane Group suggested the same treatment combination, however, with streptomycin as the aminoglycoside of choice 28 .…”
Section: Treatmentmentioning
confidence: 99%
“…Con respecto al tratamiento antimicrobiano utilizado en esta serie de pacientes, predominaron los esquemas asociados y prolongados, en concordancia con lo que sugiere la literatura médica 15 . El esquema más utilizado en nuestros pacientes, mientras permanecieron internados, fue doxiciclina-gentamicina, y la mayoría de ellos continuó con doxiciclina-rifampicina tras el alta hospitalaria por un total de seis semanas, obteniéndose curación en todos los pacientes.…”
Section: Discussionunclassified
“…[7][8][9][10][11][12][13] Brusellozda en sık tutulan sistemlerden biri kemikeklem sistemidir. Hastalık sakroileit, periferikartrit, spondilit, paraspinal apse, bursit, osteomyelit gibi tablolarla ortaya çıkabilmektedir.…”
Section: Discussionunclassified